Education Regarding The Factors That Cause Stroke in Communities in The Working Area of Puskesmas Sei Suka - Bintang, Siti Sarah Bintang Sarah; Jehaman, Isidorus; Dey, Titin Novayanti; Berampu, Sabirin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Stroke is a clinically defined acute and focal neurological deficit syndrome caused by vascular injury (infarction, hemorrhage) in the central nervous system. The main reason for stroke occurrence is this delay is public awareness of stroke, its symptoms, risk factors, or appropriate behavior (for example, the immediate occurrence of an emergency). Various risk factors can cause stroke, and one of them is age which cannot be changed. Hypertension is the most important modifiable risk factor for stroke, although its contribution differs for different subtypes. There are many risk factors that can cause stroke, namely factors that cannot be modified such as age, gender, genetics, and can be modified such as hypertension, diabetes mellitus, smoking, alcohol consumption and substance therapy and diabetes. Physical dysfunction is one of the dominant aspects of post-stroke disability, often associated with stroke-specific disorders such as motor impairment, fatigue, spasticity, and balance problems. Implementation of community service activities is carried out through notifications via the community health center information platform with a total of 20 community members residing in the Sei Suka Community Health Center Working Area. The results of this community service activity show that the majority of participants (more than 80%) in the community do not know the factors that cause strokes in the Sei Suka Health Center Work Area.